(3OjhGf GdoMWjFIs - (3GdMWjFI , LQhd Hf ChS Hf eGdc GdYHSj, CHh edjcI,J (B45 (3g` s
(3ChdgG (B:s
(3bGd GdMWjFI hGSeg LQhd Hf ChS Hf LDjg Hf eNRhe Hf eGdc Hf ZGdH Hf bWjYI Hf YHS(B: s
(3BNQgG (B:s
(3MeOJ Edgj Cffj de CLOceG Ch ef GdNha egQHG UHjGf MLdjGf aj s
(3GdLRA GdChd (B506s
(3fSNI NRGFfjIs
(3QhGjI eMeO Hf MHjH UfYI CHj SYjO GdScQjs
(3hQOJ CjVkG JMJ Qbe (B2089 s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B118 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B129s
Keywords: (3GdCOHs